2016
DOI: 10.1002/jbm.b.33715
|View full text |Cite
|
Sign up to set email alerts
|

Drug release from liposome coated hydrogels for soft contact lenses: the blinking and temperature effect

Abstract: In this article, liposome-based coatings aiming to control drug release from therapeutic soft contact lenses (SCLs) materials are analyzed. A PHEMA based hydrogel material loaded with levofloxacin is used as model system for this research. The coatings are formed by polyelectrolyte layers containing liposomes of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) and DMPC + cholesterol (DMPC + CHOL). The effect of friction and temperature on the drug release is investigated. The aim of the friction tests is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Several methods have been suggested to produce coatings on drug-eluting biomedical devices (e.g., layer-by-layer deposition, spray coating, dip coating, plasma-assisted grafting) with the purpose of implementing drug-eluting reservoirs [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Besides, these coatings may be used in order to increase the hydrophilicity of the device surface [ 74 ] and, also, as diffusion barriers to drug release [ 75 , 76 , 77 ]. The main concern with the design of coatings to be applied onto CLs or IOLs is the preservation of the optical properties of the original lenses.…”
Section: Drug Loading Methodsmentioning
confidence: 99%
“…Several methods have been suggested to produce coatings on drug-eluting biomedical devices (e.g., layer-by-layer deposition, spray coating, dip coating, plasma-assisted grafting) with the purpose of implementing drug-eluting reservoirs [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Besides, these coatings may be used in order to increase the hydrophilicity of the device surface [ 74 ] and, also, as diffusion barriers to drug release [ 75 , 76 , 77 ]. The main concern with the design of coatings to be applied onto CLs or IOLs is the preservation of the optical properties of the original lenses.…”
Section: Drug Loading Methodsmentioning
confidence: 99%
“…A popular approach is to coat the exterior of the contact lens in liposomes. Dimyristoylphosphatidylcholine and cholesterol liposomes have been coated onto HEMA-based hydrogels by depositing a layer-by-layer polyion solution to electrostatically sandwich the liposomes in place [258]. The liposomes did not contain drugs themselves.…”
Section: Liposomesmentioning
confidence: 99%
“…As the drug concentration increased, it could be observed that the gels turned hazy and almost opaque [29], resulting in a reduction in lens light transmission. A study carried out by Paradiso et al [90] showed that a liposome coating layer (DMPC and DPMC + CHOL, where DMPC is 1,2-dimyristol-sn-glycero-3-phosphocholine and CHOL is cholesterol) on top of a hydrogel, did not substantially alter their optical transparency (values were all above 95%). This was due to the small size of liposomes, with an average size of 103 ± 8 nm.…”
Section: Optical Transparencymentioning
confidence: 99%
“…The incorporation of NPs could influence the lens' ability to transmit light significantly because the nanosized particles could diffract and scatter the incident light. Several studies indicated that the transparency of the CLs was not affected when the NP size was below 180 nm [71,90,91]. However, NPs of size around 300 nm were shown to reduce the lens optical clarity.…”
Section: Optical Transparencymentioning
confidence: 99%